Preliminary investigation on the flexural behaviour of steel fibre reinforced self-compacting concrete ribbed slab / Nur Aiman Suparlan … [et al.] - Suparlan, Nur Aiman; Ku Ayob, Muhammad Azrul; Ahmad, Hazrina; Hamzah, Siti Hawa; Mohd Hashim, Mohd Hisbany (Institute of Research Management and Innovation (IRMI), 2018)
A ribbed slab structure has the advantage in the reduction of concrete volume in between the ribs resulting in a lower structural self-weight. In order to overcome the drawbacks in the construction process, the application of steel fibre self-compacting concrete (SCFRC) is seen as an alternative material to be used in the slab. This preliminary investigation was carried out to investigate the flexural behaviour of steel fibre selfcompacting concrete (SCFRC) as the main material in ribbed slab omitting the conventional reinforcements. Two samples of ribbed slab were prepared for this preliminary study; 2-ribbed and 3-ribbed in 1 m width to identify the effect of the geometry to the slab’s flexural behaviour. The dimension of both samples is 2.5 m x 1 m with 150 mm thickness. The compressive strength of the mix is 48.6 MPa based on the cubes tested at 28 days. Load was applied to failure by using the four point bending test set-up with simple support condition. The result of the experiment recorded ultimate load carrying capacity at 30.68 kN for the 2-ribbed slab and 25.52 kN for 3-ribbed slab. From the results, the ultimate load of the 2-ribbed sample exceeds 3-ribbed by approximately 20%. This proved that even with lower concrete volume, the sample can still withstand an almost similar ultimate load. Cracks was also observed and recorded with the maximum crack width of 2 mm. It can be concluded that the steel fibres do have the potential to withstand flexural loadings. Steel fibre reduces macro-crack forming into micro-cracks and improves concrete ductility, as well as improvement in deflection. This shows that steel fibre reinforced self-compacting concrete is practical as it offers good concrete properties as well as it can be mixed, placed easier without compaction.